2014
DOI: 10.5505/agri.2014.76993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the postoperative analgesic efficacy of an ultrasound-guided fascia iliaca compartment block versus 3 in 1 block in hip prosthesis surgery

Abstract: We believe that the safe and efficient application of the ultrasound-guided 3 in 1 block and the FICB is necessary in multimodal analgesic treatment in order to enable postoperative analgesia in hip prosthesis surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 16 publications
(32 reference statements)
6
45
3
1
Order By: Relevance
“…All patients received general anesthesia for surgery. Four articles [1114] reported that TJAs were performed by same teams. Three studies [11,13,15] received premedication for pain relief.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients received general anesthesia for surgery. Four articles [1114] reported that TJAs were performed by same teams. Three studies [11,13,15] received premedication for pain relief.…”
Section: Resultsmentioning
confidence: 99%
“…[1114] A fixed-effects model was used because no significant heterogeneity was found among these studies ( χ 2  = 0.56, df = 3, I 2  = 0%, P  = .906). The pooled results demonstrated that there was no significant difference in opioids consumption at 24 hours between groups (SMD = 0.037, 95% CI: −0.212 to 0.286, P  = .771; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] However, as the FICB was performed under real-time ultrasound guidance, the success rate was increased to 82% to 87%, leading to an increased interest in FICB as a postoperative analgesia option for hip and knee surgical procedures. [2,3] …”
Section: Introductionmentioning
confidence: 99%
“…The sensorial innervation of the hip is provided by the nerves in the lumbar plexus and sacral plexus (42). Although whether lumbar or sacral plexus have a primary effect on sensorial innervation of the hip remains unknown, according some previous studies (39,40) and the present study, the lumbar plexus block can provide effective analgesia.…”
Section: Discussionmentioning
confidence: 99%